Trends in age at menarche and adult height in selected African countries (1950-1980) - Michel Garenne (Taylor & Francis Group, 2020)
Background: The mean age at menarche remains poorly documented in Africa. Aim: To document levels, trends, and determinants of mean age at menarche in selected African populations. Subjects and methods: The World Fertility Surveys recorded the age at menarche in 12 African countries. These surveys were conducted from 1977 to 1983 and were based on large representative samples of national populations. Demographic and Health Surveys provided trends in adult height for the same cohorts. Results: The mean age at menarche was higher in sub-Saharan Africa (14.5 years) than in North-Africa (13.5 years). Age at menarche was declining significantly in all sub-Saharan African countries, but only in one North-African country. The speed of decline in sub-Saharan Africa averaged 0.47 years for a 30-year period, comparable to the speed of decline in Europe. Sub-Saharan African countries with higher increase in female adult height also had larger declines in mean age at menarche. In multivariate analysis, trends in age at menarche were correlated with trends in adult height and child survival. Conclusion: In sub-Saharan Africa, age at menarche was undergoing a transition similar to that of European countries in the nineteenth century and was associated with improving health of young women. North-African countries were more advanced.